Surgical procedure and treatment results of pharyngoplasty CWICKs for obstructive sleep apnea. Issue 4 (August 2022) - Inoue, Daisuke; Chiba, Shintaro; Kondo, Minori; Ikeda, Konomi; Watanabe, Subaru; Kitamura, Koichi; Yagi, Tomoko; Tar, Toh Song; Capasso, Robson
Abstract: Objective: Uvulopalatopharyngoplasty (UPPP) is performed as a surgical treatment at the oropharyngeal level for obstructive sleep apnea, but there are problems with variations in treatment effects and postoperative complications. Therefore, to improve those, we have devised and put into practice the so-called CWICKs, which is a modified version of barbed reposition pharyngoplasty as a surgical method. We outline the procedure of CWICKs and report the treatment results in comparison with the conventional UPPP. Methods: CWICKs are surgeries that use resorbable wound closure devices to pull the posterior palatal arch outward and elevate it anteriorly and superiorly to maintain an open upper airway during sleep at the soft palate level. We compared the therapeutic effects of 46 patients evaluated by polysomnography before and after surgery among CWICKs performed in our department between January 2015 and December 2019 and 91 patients who underwent UPPP in our department between January 2000 and December 2008. Results: In 46 patients who underwent CWICKs, significant improvement was observed before and after surgery using the apnea hypopnea index (AHI), obstructive apnea index (OAI), ration of each sleep stage, and SpO2 level > 90%. The improvement rate of AHI was 68.4%, and the surgical success rate was 58.7%. Postoperative patient satisfaction was also good, and significant improvement in subjective sleepiness (Epworth Sleepiness Scale) and subjective sleep quality (Pittsburgh Sleep Quality Index) was observed before and after surgery. No postoperative complications such as dysphagia or scar stenosis were observed in any of the patients in the CWICKs group. Compared with the 91 cases of UPPP, which is the conventional method, there was no significant difference in the improvement rate of AHI (p = 0.199), but the improvement rate of OAI had significantly improved (p = 0.013). Regarding the postoperative sleep stage, In the CWICKs group, a significant decrease in stage 1 and a significant increase in stage 2, stage 3, and stage rapid eye movement were observed, whereas in the UPPP group, no significant improvement in stage 3 was observed. Multivariate analysis of surgical success did not show an association with surgical methods (CWICKs or UPPP). On the other hand, an association was shown with age (<45), palatine tonsil size (≥3 / 5), high MPH (≥14 mm), and OAI rate (> 1/3). Conclusion: The treatment outcome of CWICKs was equal to or better than that of the conventional UPPP. Future follow-up is required for long-term prognosis, but no serious postoperative complications, such as dysphagia or scar stenosis, have been observed. CWICKs are considered to be minimally invasive, simple, and effective surgical procedures with few complications.